DNA Barcode, chemical analysis, and antioxidant activity of Psidium guineense from Ecuador - Joel Eduardo Vielma-Puente; Efrén Santos-Ordóñez; Xavier Cornejo; Iván Chóez-Guaranda; Ricardo Pacheco-Coello; Liliana Villao-Uzho; Christian Moreno-Alvarado; Natalia Mendoza-Samaniego; Yuraima Fonseca (PLoS ONE, 2025)
This study investigates the phytochemical, genetic, and antioxidant properties of Psidium guineense, a species native to the tropical dry forests of Ecuador. Leaves were collected, preserved in recognized herbaria, and subjected to Soxhlet extraction using polar and non-polar solvents. Phytochemical screening revealed the presence of secondary metabolites, while GC-MS analysis detected chemical compounds in the extracts. Antioxidant assays demonstrated high phenolic (54.34 ± 0.49 mg GAE/g) and flavonoid (6.43 ± 0.38 mg QE/g) content, with significant antioxidant activity in DPPH (0.57 ± 0.04 mg TE/g), FRAP (105.52 ± 6.85), and ABTS (1.25 ± 0.01 mg TE/g) assays. DNA barcoding of nine loci, (seven from the chloroplast genome and two nuclear genome) using a CTAB extraction protocol and PCR, provides the first genetic characterization of this species, contributing to genetic diversity assessments and phylogenetic studies. These findings underscore the importance of P. guineense as a source of potent bioactive compounds with significant antioxidant potential, highlighting its applicability in nutritional and pharmaceutical industries. Additionally, the genetic insights gained support efforts to expand DNA barcoding databases for tropical biodiversity conservation.